Spectrum of periorbital dermatoses in a tertiary care centre in Puducherry - Indradevi, R.; Oudeacoumar, P.; Medasani, Varsha; Rao, Chitralekhya (International Journal of Research in Dermatology, 2017)
Background: Periorbital dermatoses are dermatological manifestations of the area around the eyes. They are the most commonly encountered dermatoses in routine dermatological practice posing both diagnostic and therapeutic challenge for dermatologists due to the similarity of symptoms and close proximity to the eyeball. In the present study, our aim is to study the spectrum of periorbital dermatoses in a tertiary care centre in Puducherry. Methods: This was a hospital based study in which all the patients attending dermatology OPD irrespective of their age and sex were screened for periorbital dermatoses over a period of 1 year from February 2016 to January 2017. Screening resulted in 300 consenting patients with periorbital lesions. They were subjected to detailed history followed by clinical examination and relevant laboratory investigations. Clinical photographs of all patients were taken. Results: The most common dermatological conditions observed in periorbital region in our study were tumours (benign and malignant) (26.3%) followed by pigmentation (19.3%), eczema (17.3%), infections (13%), nevoid condition (10%), connective tissue disorders (2.6%), miscellaneous conditions (8.2%). Certain periorbital dermatoses were significantly more in females compared to males such as skin tags, periorbital hyperpigmentation, connective tissue diseases. Conclusions: The present study highlights the pattern of specific dermatoses in our hospital.